Dinamika dan Problematika Politik Hukum Lembaga Penyelesai Sengketa Hasil Pemilihan Kepala Daerah di Indonesia - Nasrullah Nasrullah; Tanto Lailam (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2017)
The success of free and fair local elections is not only measured by the voting process, but also determined on how the settlement of the disputes follows it. In connection with that, the institutional dispute settlement of local elections in Indonesia has experienced ups and downs that have not been interminable. The issuance of the Act Number 10 of 2016 which mandates the establishment of special judicial body for settlement of regional head election disputes still leaves a ‘homework’ of the shape or design of that special judicial institution, its authorities and procedural law that must be established ahead of national simultaneous elections in 2027. This paper is the result of a normative research with statute, analytical, and case approaches regarding the background of the existence of special judicial body which is needed to be established to resolve regional head election disputes in Indonesia as an antithesis on the weaknesses and problems ofinstitutional settlement of regional head election disputes that been there for years, namely: Supreme Court and the Constitutional Court. In order to provide an overview as well as an alternative institutional model of special court for regional head election disputes settlement to be formed onward.